The modern aerosol retrieval algorithms based on the simultaneous measurements of the intensity and polarization of reflected solar light: a review - Kokhanovsky, Alexander A. (Frontiers in Environmental Science, 2015)
In this paper the algorithms to retrieve atmospheric aerosol properties using spaceborne observations are reviewed. The main focus is on the algorithms based on simultaneous measurements of the intensity and degree of polarization of reflected solar light at the top-of-atmosphere.